Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. An Analysis of the Impact of Digital Transformation on the Unemployment Rate in the Kingdom of Saudi Arabia during the period (2000-2021) Mrs. Fatimah Fahd Alateeg, Mrs. Abrar Adel Halawani 2. The contribution of administrative information systems in providing services to trainees at the Institute of Public Administration in Riyadh, Kingdom of Saudi Arabia Mr. Ahmed Saud Alakeel 3. The impact of digital transformation on the overall performance of The Ministry of Finance – Gaza Mrs. Israa Jomaa Ahmed Abu Lehea 4. The role of diplomatic means in the settlement of international disputes Mr. El-Moatazbellah Mohamed Mohamed Noureldin 5. Measuring the quality of services provided by Mobily and its impact on the satisfaction of the pilgrims Mr. Saleh Matrouk Hamed Alosaimi 6. Measuring the Impact of Economic Variables on the Stock Market in Saudi Arabia: An Analytical Study from 2000 – 2021 Mr. Ahmad Saeed Basilim, Dr. Basel Yasser Balila 7. Economic factors affecting rice imports in Kingdom of Saudi Arabia during the period from (1989-2018) Mrs. Buthaynah Hashim Al-Hassan, Co-Prof. Samar S. Mohamed Abdalla, Co-Prof. Raga M. Elzaki 9. Convergence between the Marketing System & AI (The beginnings of the IR 5.0 & the birth of Algorithmic Marketing Age) Co-Prof. Tarek Ahmed Guendouz